Long Memory and Level Shifts: Re-Analyzing Inflation Rates - Charles S. Bos; Philip Hans Franses; Marius Ooms (Tinbergen Institute, 1998)
A key application of long memory time series models concerns inflation. Long memory implies that shocks have a long-lasting effect. It may however be that empirical evidence for long memory is caused by neglecting one or more level shifts. Since such level shifts are not unlikely for inflation, where the shifts may be caused by sudden oil price shocks, we examine whether evidence for long memory (indicated by the relevance of an ARFIMA model) in G7 inflationrates is spurious or exaggerated. Our main findings are that apparent longmemory is quite resistant to level shifts, although for a few inflation rates we find that evidence for long memory disappears.
Keywords: 330; Long memory; fractional integration; structural change; inflation; Inflation; Zeitreihenanalyse; Theorie; USA